Impact of Online Games on Children's Mental Health - Kevin Guerada (Newinera Publisher, 2021)
This article examines the impact of online games on children's mental health. A person can be diagnosed with a game addiction by a psychologist or a psychiatrist if he has a game playing pattern that is severe enough to have a negative impact on himself, his family, social, education, work, and other important things. Psychologists or psychiatrists usually can only provide a diagnosis after a person's game addiction pattern lasts for at least 12 months, although this time requirement can be shortened if the adverse effects of playing games on his daily life are very obvious. The impact of online gaming addiction on children is manifested through a lack of focus on other daily activities, lack of attention in class, and constant thinking about games. In fact, the World Health Organization (WHO) has designated online game addiction as a type of mental disorder. Game addiction can also occur with other mental disorders, such as stress, depression and anxiety disorders. Various efforts can be made to prevent mental disorders, namely doing physical activity and staying physically active, helping others sincerely to maintain positive thoughts.